RANCANGAN SISTEM PENILAIAN HASIL KINERJA MULTI COMPANY DAN CROSS BUSINESS SECTOR - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
Each agency has its own characteristics and given authority in managing its finances. Foundation education and welfare PT.PLN (Persero) (YPK-PLN) has 14 affiliated companies. Each affiliate is required to report their financial periodically to YPK-PLN. The diversity of business fields and different locations makes YPK-PLN difficult to obtain financial position data on each affiliate. This financial report becomes one of the YPK-PLN reference to see the state of its subsidiary. The financial statements should be reported quarterly in a year. These financial statements include the balance sheet financial statements, labels and flows. The purpose of this study is to design and build a system that can unify all the financial statements of each affiliate and then calculated the results of its performance. The result of its performance is calculated dimasksud Operating Ratio, Average Collection Period, Return on Equity, Net Profit Margin, Current Ratio and Debt to Equity Ratio. This research was conducted with waterfall methodology to develop the software. To design the system to be built will use UML 2.0. In the development of the software will be used php language with codeigniter framework. The database used is SQL DBMS MariaDB with Apache 2 as its web server. The results also proved that the Performance Results of the affiliate financial ratios have an important role for YPK-PLN in determining whether to invest shares in the company concerned is the right decision.